Geopolitical Risk & Indonesian Stock Market Response - Saputra, Sahdan; Dwi Putri Marswandi, Ega; Hendri, Wira (Jurnal Ecoment Global, 2023)
Objective: The aim of this research is to determine empirically the impact of geopolitical risk originating from countries with high geopolitical risk and domestic ones on the Composite Stock Price Index in Indonesia. In addition, this research aims to determine the role of geopolitical actions in strengthening or weakening the relationship between geopolitical risk and the Composite Stock Price Index in Indonesia. Design/Methods/Approach: This research uses geopolitical risk index (GPRH) data from countries with the highest geopolitical risk index in the last 3 years and domestic ones consisting of Ukraine, Russia, America, China and Indonesia. Meanwhile, geopolitical action risk (GPRA) is a risk index measured in aggregate from January 2004-October 2023, so the number of observations in this study reached 238. Findings: The findings in the research show that Ukraine and America have a negative and significant influence, while China and Russia have a positive and significant impact on the composite stock price index in Indonesia. Apart from that, this research also found that the influence of geopolitical risk on the composite stock price index in Indonesia is greater when geopolitical actions such as escalation of war and acts of terror occur.   Originality/Value: This research complements several previous studies regarding the impact of geopolitical risk on the Indonesian composite stock price index. Several previous studies have not examined the impact of each country's geopolitical risk on the composite stock price index and how it is moderated by geopolitical action. Practical/Policy implication: The findings in this research prove that countries that have high geopolitical risk have a significant influence on the Composite Stock Price Index in Indonesia. So that investors can use this research as a consideration when investing in the capital market by considering geopolitical risks originating from abroad and domestically.